Effect of Dairy Manure Storage Conditions on the Survival of E. coli O157:H7 and Listeria. Issue 1 (1st January 2018) - Biswas, S.; Niu, M.; Pandey, P.; Appuhamy, J. A. D. R. N.; Leytem, A. B.; Kebreab, E.; Dungan, R. S.
Abstract : Dairy manure is regularly applied to crop fields as a solid or liquid to improve the soil nutrient status. However, pathogens may survive during manure storage and enter the environment during application. In this study, three storage practices were evaluated to understand the survival patterns of Eschericia coli O157:H7 and Listeria spp. in dairy manure using a culture‐based approach. To replicate common farm manure storage techniques, solid manure was stacked as piles with periodic turning or as static piles without turning, whereas liquid manure (feces, urine, and water) was stored as a slurry in small tanks to simulate lagoon conditions. The E. coli and Listeria levels in the manure samples were determined for 29 wk. Results showed that there was an initial reduction in bacteria levels in the first month; however, both E. coli and Listeria managed to survive in the solid manure piles for the full study period. In slurry samples, E. coli was not detected after 14 wk, but Listeria survived until the end of the experiment at relatively lower levels than in the solid manure piles. Ambient weather and pile size were identified as the main reasons for bacteria survival during the course of the experiment. The outcome of this study is important in terms of understanding pathogen survival in manure piles and slurries prior to their application to crop fields. Core Ideas: Solid and liquid dairy manure storage conditions on pathogen decay were investigated. E. coli O157:H7 and Listeria spp. survived in solid manure up to 6 months. Pile size and temperature are factors that likely influenced pathogen survival.